Handbook of Renal Biopsy Pathology - Howie, Alexander J.; SpringerLink (Online service) (New York, NY : Springer New York, 2008)
This practical handbook provides a short, clear and useful guide to interpretation of renal biopsy specimens. It is intended to be useful to pathologists, pathologists-in-training, nephrologists, nephrologists-in-training and medical students. Alexander J. Howie, M.D., is Professor of Renal Pathology, University College London, London, United Kingdom.
General Points About Renal Biopsy Specimens -- Technical Handling of Renal Biopsy Specimens -- How to Look at a Renal Biopsy Specimen: Preliminary Study -- How to Look at a Renal Biopsy Specimen: Initial Study of the Kidney -- Indication for Biopsy: Nephrotic Syndrome -- Indication for Biopsy: Acute Renal Failure -- Indication for Biopsy: Chronic Renal Failure -- Indication for Biopsy: Hematuria -- Indication for Biopsy: Proteinuria -- Indication for Biopsy: Renal Allograft -- Other Indications for Biopsy of Kidneys.
Keywords: Medicine; Nephrology; Pathology; Medicine & Public Health; Pathology; Nephrology; Electronic books